PENGARUH PENERAPAN METODE PEMBELAJARAN TALKING STICK TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 16 PADANG - Warman, Gustia; Rahmi, Rahmi; Melisa, Melisa (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The background of this research is that the students mathematical concept apprehensions are low. The purposes of this research is to how the activity of the students in the learning process of mathematics by applying the talking stick learning methods and to know whether the students mathematical concept apprehensions by applying the t the talking stick learning methods is better than that using the conventional learning for the VIII-grade students of SMPN 16 Padang. This is experimental research with Random to Subject design. The population in this research is the VIII-grade students of SMPN 16 Padang of the year 2013/2014, except for VIII1 class. The technique of sample classes were determined randomly. The instrument used in this research is the observation sheet activities and test for the mathematical concept apprehension.Based on the observation, an increase inÂ the activity of student learning. Based on the results of data analysis, it is known that both sample classes distribute normally and homogenously. So that the hypothesis is accepted, that means that the studentsâ mathematical concept apprehension using the talking stick learning methods is better than that using the conventional learning for the VIII-grade students of SMPN 16 Padang.